Genotypic and Antimicrobial Susceptibility of Carbapenem-resistant Acinetobacter baumannii: Analysis of ISAba Elements and blaOXA-23-like Genes Including a New Variant - Bahador, Abbas; Raoofian, Reza; Pourakbari, Babak; Taheri, Mohammad; Hashemizadeh, Zahra; Hashemi, Farhad B. (Frontiers in Microbiology, 2015)
Carbapenem-resistant Acinetobacter baumannii (CR-AB) causes serious nosocomial infections, especially in ICU wards of hospitals, worldwide. Expression of blaOXA genes is the chief mechanism of conferring carbapenem resistance among CR-AB. Although some blaOXA genes have been studied among CR-AB isolates from Iran, their blaOXA-23-like genes have not been investigated. We used a multiplex-PCR to detect Ambler class A, B, and D carbapenemases of 85 isolates, and determined that 34 harbored blaOXA-23-like genes. Amplified fragment length polymorphism (AFLP) genotyping, followed by DNA sequencing of blaOXA-23-like amplicons of CR-AB from each AFLP group was used to characterize their blaOXA-23-like genes. We also assessed the antimicrobial susceptibility pattern of CR-AB isolates, and tested whether they harbored insertion sequences ISAba1 and ISAba4. Sequence comparison with reference strain A. baumannii (NCTC12156) revealed five types of mutations in blaOXA-23-like genes; including one novel variant and four mutants that were already reported from China and the USA. All of the blaOXA-23-like genes mutations were associated with increased minimum inhibitory concentrations (MICs) against imipenem. ISAba1 and ISAba4 sequences were detected upstream of blaOXA-23 genes in 19 and 7% of isolates, respectively. The isolation of CR-AB with new blaOXA-23 mutations including some that have been reported from the USA and China highlights CR-AB pervasive distribution, which underscores the importance of concerted national and global efforts to control the spread of CR-AB isolates worldwide.